A transcriptional program associated with cell cycle regulation predominates in the anti-inflammatory effects of CX-5461 in macrophage - Wang, Jie; Zheng, Zhijian; Cui, Xiaopei; Dai, Chaochao; Li, Jiaxin; Zhang, Qunye; Cheng, Mei; Jiang, Fan (Frontiers in Pharmacology, 2022)
CX-5461, a novel selective RNA polymerase I inhibitor, shows potential anti-inflammatory and immunosuppressive activities. However, the molecular mechanisms underlying the inhibitory effects of CX-5461 on macrophage-mediated inflammation remain to be clarified. In the present study, we attempted to identify the systemic biological processes which were modulated by CX-5461 in inflammatory macrophages. Primary peritoneal macrophages were isolated from normal Sprague Dawley rats, and primed with lipopolysaccharide or interferon-gamma. Genome-wide RNA sequencing was performed. Gene Ontology and Kyoto Encyclopedia of Genes and Genomes databases were used for gene functional annotations. Enrichment analysis was conducted using the ClusterProfiler package of R software. We found that CX-5461 principally induced a molecular signature related to cell cycle inhibition in primed macrophages, featuring downregulation of genes encoding cell cycle mediators and concomitant upregulation of cell cycle inhibitors. At the same concentration, however, CX-5461 did not induce a systemic anti-inflammatory transcriptional program, although some inflammatory genes such as IL-1beta and gp91phox NADPH oxidase were downregulated by CX-5461. Our data further highlighted a central role of p53 in orchestrating the molecular networks that were responsive to CX-5461 treatment. In conclusion, our study suggested that limiting cell proliferation predominated in the inhibitory effects of CX-5461 on macrophage-mediated inflammation.